Legal Review of the Prosecutor's Authority in Setting Aside Cases in the Criminal Justice Process - Ramdhani, Ramdhani; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. The waiver of a case is an authority, it is not impossible that the decision to waive a case can be challenged in court, to question whether in carrying out the duties and authority of the case deponeer, the Attorney General has sufficient reasons, namely: To what extent does the waiver of the case meet the requirements for the sake of public interest, namely the interests of the nation and state and/or the interests of the general public and the ideal measure of the use of the opportunity principle and which is able to provide a picture of the prosecution policy in handling criminal cases effectively, efficiently, and responsibly which is carried out without abandoning the sense of justice. The aim of this research is to find out and analyze (1) the nature of the position of the Prosecutor in the Indonesian Criminal Justice System, (2) the legal barometer of the Prosecutor's authority to set aside cases in the criminal justice process, and (3) the fundamental problems of the Prosecutor's authority to set aside criminal cases. The approach method used in this study is normative juridical. The specifications of this study are descriptive analytical. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results and discussion can be concluded: (1) In the criminal justice system, the role of the prosecutor's office is very central because the prosecutor's office is the institution that determines whether a person should be examined by the court or not. The prosecutor also determines whether a person will be sentenced or not through the quality of the indictment and charges made. (2) Article 35 letter c of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia is the legal basis for setting aside cases in the public interest as the authority of the Attorney General. The setting aside of cases in the public interest based on Constitutional Court Decision Number 29/PUU-XIV/2016, can be carried out after the obligation to pay attention to the advice and opinions of state authorities that have a relationship with the problem is carried out by the Attorney General. (3) The issuance of a deponeering decision is a debate in Indonesia both among academics and among state institutions. The debate occurs because of the diversity of opinions or it can be said that for multiple interpretations of the meaning of